The Development and Evaluation of a Strength-based Technology Club for Adolescents with Autism Spectrum Disorder - Jones, Matthew (Curtin University, 2021)
This thesis designed and evaluated computer coding clubs for autistic adolescents. The coding clubs did not aim to treat autism or ‘fix’ adolescents but rather celebrate autistic strengths and abilities. This thesis developed a strength-based framework that focused on leveraging interests, valuing strengths, encouraging autonomy, and modifying the environment to suit the individual. The club provided a place where autistic adolescents felt like they belonged, surrounded by like-minded people who shared a passion for technology.